Approximate Controllability for Time-dependent Impulsive Neutral Stochastic Partial Differential Equations with Fractional Brownian Motion and Poisson Jumps - Ramkumar, K.; Ravikumar, K.; Anguraj, A. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we investigate the approximate controllability for time-dependent impulsive neutral stochastic partial differential equations with fractional Brownian motion and Poisson jumps in Hilbert space. The results are obtained by using semigroup theory, stochastic analysis, and fixed point approach, we derive a new set of sufficient conditions for the approximate controllability of nonlinear stochastic system under the assumption that the corresponding linear system is approximately controllable. Finally, an example is provided to illustrate our results.